Free autogenous cartilage grafts to the mandible of rats-histological study. - de Tulio, S.; Okamoto, T.; Gabrielli, M. F. (My University, 1992)
The present study was designed to histologically evaluate the behavior of free autogenous cartilage grafts to the mandible of rats. A 3-mm segment was removed from the last rib of male adult rats and transplanted fresh to a receptor bed prepared on the mandibular ramus. The results showed that the grafts maintained their vitality up to 120 days and the perichondrium was biologically integrated to the osseous bed. Appositional growth of the grafts was found. New bone formation was observed in close proximity to the grafts, but newly formed trabeculae did not arise from perichondrium.
Keywords: animal; bone development; cartilage; histology; male; mandible; physiology; rat; rat strain; time; transplantation; Animal; Cartilage; Male; Mandible; Osteogenesis; Rats; Rats, Wistar; Time Factors